Early-stage drug discovery in a new-generation ultrahigh-throughput mass spectrometry platform - Nicolás M. Morato; Yunfei Feng; Kitmin Chen; Kai-Hung Huang; Alexis Owen; Joseph V. Caruso; Beinan Yang; Samadhi C. Kulathunga; Andrew D. Mesecar; Carleen Klumpp-Thomas; Aco Radujevic; Alexander G. Godfrey; et al. (Proceedings of the National Academy of Sciences, 2026)
Early-stage drug discovery involves a complex set of processes that typically requires iterative exploration of a vast chemical-biological search space. Over the past few decades, these processes have been facilitated using automated experimentation in the form of high-throughput screening technologies for hit discovery via large-scale biochemical assays of candidate libraries. However, optimized generation of small-molecule candidates is still largely limited to traditional synthetic chemistry workflows, thus representing a bottleneck in the discovery endeavor. Here we describe and demonstrate the capabilities of a next-generation automated ultrahigh-throughput system based on desorption electrospray ionization (DESI) mass spectrometry (MS), which consolidates key activities of early drug discovery: i) organic reaction screening for routes to new candidates, ii) small-scale synthesis following optimized reactions, and iii) bioactivity assessment of the newly generated compounds in a direct-to-biology (i.e., product purification-free) fashion. Importantly, the first two synthetic steps leverage accelerated reactions in microdroplets for on-the-fly synthesis followed by in operando MS analysis or small-scale collection, whereas the later bioanalytical application relies on the label-free nature of MS as well as the contactless and complex-matrix-tolerant nature of DESI. Altogether, this fully automated technology, which has a combined synthetic/analytical throughput of up to ~3 Hz using (sub)nanogram sample amounts (and ca. 6 mHz at the milligram-level synthetic scale), has the potential to accelerate translational efforts via a single-platform closed-loop discovery cycle whose main aspects are illustrated herein, including the demonstration of increases in the biological activity of drug-substance analogs generated in the course of a complete DESI-based direct-to-biology campaign.